Pemikiran Pendidikan Islam KH. Muntaha Al Hafidz dalam Buku Charismatic Leadership Karya Dr. Faisal Kamal., M.Pd.I. - Cahya Nofiani; Pamungkas Stiya Mulyani; Faisal Kamal (Jurnal Mahasiswa Kreatif, 2024)
This thesis aims to find out the contents of the Charismatic Leadership book: The Role, Thought & Life View of KH. Muntaha Wonosobo, knowing the thought of Islamic education from the perspective of KH. Muntaha al Hafidz, as well as knowing the impact of KH's thinking. Muntaha alHafiz. This research is qualitative research, where the type of research is library research with data collection techniques using documentation methods and online searches. Then, the data source was obtained from primary data derived from the Charismatic Leadership book: The Role, Thought & Life View of KH. Muntaha Wonosobo and secondary (thesis education books, articles, internet sites, and journals). The analysis techniques used are content analysis techniques, discourse analysis, and D&C (Devide and Conquer) analysis. Based on the results of this study, it can be concluded that the Charismatic Leadership book contains the struggle of KH. Muntaha al Hafidz developed Islamic education with several strategies, namely the integration of general knowledge and religion, the establishment of formal educational institutions, and teaching methods that are made modern and relevant to this day. Islamic educational thought KH. Muntaha al Hafidz is with educational innovations that combine formal and non-formal education to be in harmony between imtaq (faith and taqwa) and science and technology (science and technology). While the impact of KH's thinking. Muntaha al Hafidz is that economic status increases, people are aware of the importance of education, the birth of professional groups, and make Islamic education integrated.